Isolation of Aspergillus ochraceus and Production of Ochratoxin in Coffee Samples - Pandit, Pratikshya; Panta, Om Prakash; Karki, Tika Bahadur (Nepal Journal of Science and Technology, 2015)
The occurrence of mycotoxins in foods and feeds has long been recognized as a potential hazard for human and animal health due to their severe toxic and carcinogenic properties. Among various mycotoxins, ochratoxin A (OTA) is the most hazardous one because of its serval contamination cases in the world. In this study contamination levels of Aspergillus ochraceus in coffee samples were assessed, where two strains of it were isolated from 65 coffee samples. They were confirmed by using Czapeck yeast extract agar (CYA). Fermentation was carried out for ochratoxin production at different moisture levels: 20%, 40% and 60% by using coffee as a substrate. The extract was assayed for the presence of ochratoxin by thin layer chromatography (TLC). Results showed that high production of this toxin (402 ppb) was obtained in coffee containing 60% of moisture after 19 days of incubation period with high load of fungal growth and the effect of roasting on coffee containing ochratoxin was observed where the level of it was decreased after roasting. It can be concluded that coffee substrate with high level of moisture favored good condition for the growth of A. ochraceus and ochratoxin formation. DOI: http://dx.doi.org/10.3126/njst.v15i1.12030 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 133-138